Friedrich Creuzer (1771-1858) à l’Académie des Inscriptions et Belles-Lettres - Sotera Fornaro (Flaubert: Revue Critique et Génétique)
This essay is an overview of the cultural and personal context, that determined the fortune of Friedrich Creuzer's (1771-1858) work Symbolik und Mythologie. His election as member of the Académie des Inscriptions et Belles-Lettres in 1825 is the main episody of this story and should be understood in the frame of the German-French “cultural transfer”.